Influence of experimental variables on thermally stimulated recovery results: analysis of simulations and real data on a polymeric system - Alves, N. M. (2002)
Thermally stimulated recovery (TSR) is a low frequency mechanical spectroscopy technique that allows investigation of conformational mobility in polymeric systems. In this study the effect of initial parameters chosen to perform experiments on the TSR response of a material in the thermal sampling mode is investigated. The studied experimental parameters are creep time (tσ) recovery time (tr) and window width (ΔTw); all are independently changed at one constant creep temperature. A simple model, able to describe global TSR and TS measurements, is used to evaluate the influence of each of the different parameters. The simulations are conducted for a system with a uniform distribution of activation energies and a fixed pre-exponential factor. These simulation results are qualitatively compared with some experimental data obtained for semicrystalline poly(ethylene terephthalate) under different conditions in the glass transition region. The tendencies resulting from the influence of the studied parameters on the intensity, the position of the TS peaks and the corresponding activation energies are found to be the same for the experimental and simulated results. Only the variation of the activation energy with tσ is opposite to that observed with the modelling results; this feature is explained on the basis of structural relaxation effects.